2019
DOI: 10.1161/circep.119.007336
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Baseline Impedance

Abstract: Background-Radiofrequency ablation (RFA) of intramural ventricular substrate is often limited by insufficient tissue penetration despite high energy settings. As lesion dimensions have a direct and negative relationship to impedance, reducing the baseline impedance may increase the ablation effect on deep ventricular tissue. Methods-This study included 16 patients with ventricular tachycardia (VT) or frequent ventricular premature complexes (VPCs) refractory to ablation with irrigated catheters. Following a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“… 12 Prior clinical studies have suggested reducing baseline impedance can improve current delivery during RFCA by changing the location or number of dispersive electrodes, which may facilitate successful ablation in intramural ventricular substrates. 17 While most electrophysiology laboratories place the DP on the patient’s back, flanks, or thigh, some groups have advocated placing the DP anteriorly on the chest. A recent pilot study compared the anterior and posterior positions of the DP during AF ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Prior clinical studies have suggested reducing baseline impedance can improve current delivery during RFCA by changing the location or number of dispersive electrodes, which may facilitate successful ablation in intramural ventricular substrates. 17 While most electrophysiology laboratories place the DP on the patient’s back, flanks, or thigh, some groups have advocated placing the DP anteriorly on the chest. A recent pilot study compared the anterior and posterior positions of the DP during AF ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Remote factors, such as the amount of SAT underneath the DP, may affect the baseline impedance and hence the lesion size. 12 , 17 There are no conclusive data about differences of subcutaneous fat in anterior and posterior side. For instance, Störchle et al 18 found a difference of 3 mm greater thickness of anterior fat compared to posterior fat above fibrous septae.…”
Section: Methodsmentioning
confidence: 99%
“…When using novel forms of energy delivery for achieving the increased tissue depth required for VT ablation, there is a balance between efficacy and risk. 8 Use of low-ionic irrigants may increase tissue depth but has been associated with steam pops. 4 Bipolar ablation between 2 catheters has been used but is also reported to be associated with steam pop, perforation, and clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, more recent preclinical data have demonstrated that depths approaching 15 mm can be achieved with ULTC in ventricular tissue. 8 The first-in-human cavotricuspid isthmus ablation using ULTC demonstrated its capability as an effective energy source for typical flutter ablation. 7 Data from Cryocure-2 reported 85% freedom from atrial fibrillation at 12 months in patients with persistent atrial fibrillation after a single ULTC procedure.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation